Provenance as a knowledge organization principlet - Tognoli, Natalia; Chaves Guimarães, José Augusto [UNESP] (IMR Press, 2019)
The principle of provenance is one of the most important milestones in archival practice and theory from the time its establishment grounded the scientific dimension of archival discipline in the nineteenth century. Since then, provenance and document context have supported the organization of archival knowledge (especially through classification and description procedures). Such relationships were gradually refined over the years and from different experiences between European archives and their classification and ordering systems. Historically, the principle of provenance is a pivotal moment in the development of archival theory, crucial to understanding the nature of records and archives. However, in archival theory, the principle of provenance still does not correspond to a single term or a single definition and scarce normalization terminology remains one of the problems of archival science, which leads to a lack of consensus about the division between the two principles of provenance and original order. Recently, the concept of provenance has been addressed by many other disciplines flaw, library and information science, computer science and visual analytics) and applied to different domains (cloud-based storage, preservation of digital records, digital evidence, digital humanities, e-science, open data, linked data, knowledge organization and indexing. As the use of provenance reaches new domains it is no longer just an organizing principle but also a means of reaching for authenticity and reliability of data and objects in digital environments or museums or to reestablish the original organic relationship in library collections.
Keywords: Archival; Fonds; Order; Principle; Provenance; Records